A part of patients with autism spectrum disorder has haploidy of HPC-1/syntaxin1A gene that possibly causes behavioral disturbance as in experimentally gene ablated mice. (22nd March 2017) - Kofuji, Takefumi; Hayashi, Yuko; Fujiwara, Tomonori; Sanada, Masumi; Tamaru, Masao; Akagawa, Kimio
Highlights: STX1A gene ablated mice exhibit abnormal behavioral profiles, similar to human autistic symptoms. Some ASD patients were haploid for the STX1A gene similar to STX1A heterozygote mutant mice. In ASD patients with STX1A gene haploidy, STX1A mRNA expression was reduced to about half of controls. A part of ASD patients had haploidy of STX1A gene and lower STX1A gene expression. Abstract: Autism spectrum disorder (ASD) is highly heritable and encompasses a various set of neuropsychiatric disorders with a wide-ranging presentation. HPC-1/syntaxin1A (STX1A) encodes a neuronal plasma membrane protein that regulates the secretion of neurotransmitters and neuromodulators. STX1A gene ablated mice (null and heterozygote mutant) exhibit abnormal behavioral profiles similar to human autistic symptoms, accompanied by reduction of monoamine secretion. To determine whether copy number variation of STX1A gene and the change of its expression correlate with ASD as in STX1A gene ablated mice, we performed copy number assay and real-time quantitative RT-PCR using blood or saliva samples from ASD patients. We found that some ASD patients were haploid for the STX1A gene similar to STX1A heterozygote mutant mice. However, copy number of STX1A gene was normal in the parents and siblings of ASD patients with STX1A gene haploidy. In ASD patients with gene haploidy, STX1A mRNA expression was reduced to about half of their parents. Thus, a part of ASD patients had haploidy of STX1A gene and lower STX1A gene expression.